Ameloblastomatous CCOT: A Case Report of a Rare Variant of CCOT with a Review of the Literature on Its Diverse Histopathologic Presentation - Shailesh Menat; Shylaja MD; Kailash Attur; Kaushal Goyal (Case Reports in Dentistry)
Calcifying odontogenic cyst is considered as a rare lesion and accounts for 1% of jaw cysts. It represents a heterogeneous group of lesions which exhibit a variety of clinicopathologic and behavioral features. It has been categorized as cyst and neoplasm. Even after several classification and subclassification, COC remains an enigma. WHO classification 2005 has reclassified the lesion as calcifying cystic odontogenic tumor (CCOT). Ameloblastomatous COC is a rare variant which is not much described in the literature. This report describes one such case which was large multicystic, involved the coronoid and condylar process of the mandible, and treated by subhemimandibulectomy. The case was recurrence free even after 1 year of followup.